The Relation Between ACEI/ARB use and COVID-19 Severity in RTPCR- Confirmed Cases: A Retrospective Case-Control Study - Amaouche, Sabrina; Letaief, Ziad; Buls, Nico; Allard, Sabine; Mey, Johan de (Cardiology and Cardiovascular Medicine, 2022)
One hypothesis suggests that patients undergoing Angiotensin Converting Enzyme Inhibitor (ACEI) or Angitensin Receptor Blocker (ARB) treatment might be at greater risk for severe COVID-19 disease. This retrospective study aims to elucidate whether patients with Reverse Transcription-Polymerase Chain Reaction (RT-PCR) -confirmed Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV- 2) infection undergoing ACEI or ARB treatment present with a more severe clinical presentation or more severe lung injury than other patients, as evaluated by CT thorax scans. Comorbidities related to ACEI or ARB use, including Arterial Hypertension (AHT), Heart Disease (HD), and Diabetes Mellitus (DM), were found to be more frequent (p < 0.05) in the ACEI or ARB users’ group. The odds ratio of ACEI or ARB users for having a more severe clinical presentation was 1.12 (95% [CI] 0.59 -2.13, p = 0.741). For having a severe CT severity score (with a cut-off of 12.5 on a total score of 25), the odds ratio was 1.46 (95% [CI] 0.73 -2.94, p = 0.287). Furthermore, the odds ratio of the mortality outcome was 1.1 (95% [CI] 0.49 -2.48, p = 0.824). Although the group of ACEI or ARB users had more comorbidities, we found no significant association between CT severity, clinical severity, or mortality and the use of these drugs. These findings bolster the argument against ACEI or ARB withdrawal in COVID-19 patients.